2018
DOI: 10.1007/s00401-018-1904-1
|View full text |Cite
|
Sign up to set email alerts
|

Opposite development of short- and long-range anterior cingulate pathways in autism

Abstract: Autism has been linked with the changes in brain connectivity that disrupt neural communication, especially involving frontal networks. Pathological changes in white matter are evident in adults with autism, particularly affecting axons below the anterior cingulate cortices (ACC). It is still unknown whether axon pathology appears early or late in development and whether it changes or not from childhood through adulthood. To address these questions, we examined typical and pathological development of about 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 79 publications
(138 reference statements)
5
34
0
Order By: Relevance
“…Analysis showed that axon orientation variability appeared to be consistent across layers in OFC gray matter, but more heterogeneous than previously reported in the super cial white matter below prefrontal cortices [36]. Taken together with previous studies, our ndings show that axons become thinner and their trajectory becomes more heterogeneous, likely due to increased branching, as they transition from deep to super cial white matter, and nally enter the gray matter [27,36].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Analysis showed that axon orientation variability appeared to be consistent across layers in OFC gray matter, but more heterogeneous than previously reported in the super cial white matter below prefrontal cortices [36]. Taken together with previous studies, our ndings show that axons become thinner and their trajectory becomes more heterogeneous, likely due to increased branching, as they transition from deep to super cial white matter, and nally enter the gray matter [27,36].…”
Section: Discussionsupporting
confidence: 81%
“…Each sample yielded a large number of data points, because we typically examine a large volume fraction of the areas sampled, and thus increase the number of individual axons and neurons examined. The high sampling fraction used in our studies minimized the variability within each analyzed case, and further increased statistical power, as we have described [34][35][36][37][38]. Our previous work [5,27,[35][36][37] and power analysis showed that the sampling ratios exceed the samples needed to detect differences with a greater than 90% probability, and large effect population size (0.8) with ≤ 10% error, as recommended [39].…”
Section: Human Post Mortem Brain Tissue and Sample Sizementioning
confidence: 78%
See 3 more Smart Citations